2018
DOI: 10.1101/293001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Primate immunodeficiency virus Vpx and Vpr counteract transcriptional repression of proviruses by the HUSH complex

Abstract: Drugs that inhibit HIV-1 replication and prevent progression to AIDS do not1 eliminate HIV-1 proviruses from the chromosomes of long-lived CD4 + memory T 2 cells. To escape eradication by these antiviral drugs, or by the host immune 3 system, HIV-1 exploits poorly defined host factors that silence provirus 4 transcription. These same factors, though, must be overcome by all retroviruses, 5 including HIV-1 and other primate immunodeficiency viruses, in order to activate 6 provirus transcription and produce new … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…These findings define new functions for NP220 and the HUSH complex. The restriction is sufficiently strong that many viruses have evolved means to evade or inactivate this machinery: the Vpr and Vpx proteins from primate immunodeficiency viruses mediate degradation of the HUSH complex to relieve silencing of proviruses 15,16 , and the ICP0 gene of HSV-1 relieves HDAC-mediated silencing of viral DNA 17,18 . The silencing mechanisms and machinery uncovered here may have wide-ranging impacts on the design of non-integrating retroviral vectors for gene therapy and the gene expression following plasmid DNA transfection.…”
mentioning
confidence: 99%
“…These findings define new functions for NP220 and the HUSH complex. The restriction is sufficiently strong that many viruses have evolved means to evade or inactivate this machinery: the Vpr and Vpx proteins from primate immunodeficiency viruses mediate degradation of the HUSH complex to relieve silencing of proviruses 15,16 , and the ICP0 gene of HSV-1 relieves HDAC-mediated silencing of viral DNA 17,18 . The silencing mechanisms and machinery uncovered here may have wide-ranging impacts on the design of non-integrating retroviral vectors for gene therapy and the gene expression following plasmid DNA transfection.…”
mentioning
confidence: 99%
“…The colocalization of these two protein complexes to promoters in differentiated cells may therefore be a remnant of the developmental program (Figure 5A) [1,52]. (2) We and others have demonstrated that the degree of transcriptional silencing by HUSH is promoter-specific [3,8,14,21], and extend this observation to PRC1.6. Intrinsic properties of select exogenous and endogenous promoters such as viral origin, paused RNA Polymerase II occupancy, or transcription factor binding likely contribute to localization or activity of PRC1.6 and the HUSH complex.…”
Section: Prc16 and Hush Co-localize At Endogenous Chromatin Targetsmentioning
confidence: 64%
“…HUSH silencing of lentivectors is modulated at least in part by the promoter that drives expression of the transgene [3,8,14,21]. Both the Cas9-P2A-Puro vector used in our loss-of-function screen (Figure 2C), and the Zim3-dCas9 vector that was used to confirm the effect of L3MBTL2 (Figure 2D), are driven by EF1a promoters.…”
Section: Prc16 Is Necessary For Silencing Of a Hush-sensitive Transge...mentioning
confidence: 99%
See 1 more Smart Citation
“…For the Generation of shKAP1 HFF cell lines, 5 x 10 6 HEK 293T cells were seeded in 10-cm dishes in Dulbecco's minimal essential medium (DMEM) (Gibco) supplemented with 10 % fetal calf serum (FCS, Sigma-Aldrich), and 1 % penicillin-streptomycin (PS, Sigma-Aldrich). Utilizing the Lipofectamine 2000 reagent (Invitrogen), the cells were co-transfected on the next day with packaging plasmids pLP-VSVg (26) and pCMVdeltaR8.9 (kindly provided by T. Gramberg) together either with the plasmid pAPM-D4-miR30-L1221 (a gift from Jeremy Luban; Addgene #115846) (27) expressing a control shRNA or plasmid pAPM-D4 miR30-TRIM28 ts3 (Addgene #115864) (27) encoding for a shRNA targeting KAP1. 48 hours post transfection, the supernatant was harvested, filtered through a 0.45-μm filter and used for transduction of HFF cells.…”
Section: Generation Of Shkap1 Hff Cell Lines and Dux4 Inducible 293t ...mentioning
confidence: 99%